Antidiabetic effect of aqueous-ethanol extract from the aerial parts of Artemisia roxburghiana. Issue 5 (4th March 2022) - Kumar, Ankit; Aswal, Sonali; Chauhan, Ashutosh; Semwal, Ruchi Badoni; Singh, Randhir; Andola, Harish Chandra; Joshi, Sunil Kumar; Semwal, Deepak Kumar
Abstract: Artemisia roxburghiana is used for the management of diabetes mellitus in the Indian subcontinent. The present work aimed to validate the traditional claim of the plant in diabetes mellitus. In vitro studies were conducted using α-glucosidase and α-amylase assays whereas streptozotocin-nicotinamide-induced diabetic Wistar rats were used for in vivo study. The aqueous-ethanol extract from the aerial parts was found to exhibit α-glucosidase and α-amylase inhibitory activities with the IC50 values of 31.0 and 17.2 mg/mL, respectively when compared with acarbose (IC50 = 8.6 and 16.25 mg/mL, respectively). The extract showed a significant glucose-lowering effect in diabetic rats at the doses of 200 and 400 mg/kg in a dose-dependent manner, while acarbose (10 mg/kg) was used as a standard. The results revealed that A. roxburghiana aerial parts showed antidiabetic activity via inhibiting α-glucosidase and α-amylase enzymes. The present study also validated the ethnomedicinal claim of the plant in diabetes mellitus. Graphical abstract: